Nonallelic homologous recombination between retrotransposable elements is a driver of de novo unbalanced translocations - Robberecht, Caroline; Voet, Thierry; Esteki, Masoud Zamani; Nowakowska, Beata A.; Vermeesch, Joris R. (Genome Research, 2012)
Large-scale analysis of balanced chromosomal translocation breakpoints has shown nonhomologous end joining and microhomology-mediated repair to be the main drivers of interchromosomal structural aberrations. Breakpoint sequences of de novo unbalanced translocations have not yet been investigated systematically. We analyzed 12 de novo unbalanced translocations and mapped the breakpoints in nine. Surprisingly, in contrast to balanced translocations, we identify nonallelic homologous recombination (NAHR) between (retro)transposable elements and especially long interspersed elements (LINEs) as the main mutational mechanism. This finding shows yet another involvement of (retro)transposons in genomic rearrangements and exposes a profoundly different mutational mechanism compared with balanced chromosomal translocations. Furthermore, we show the existence of compound maternal/paternal derivative chromosomes, reinforcing the hypothesis that human cleavage stage embryogenesis is a cradle of chromosomal rearrangements.
10.1101/gr.145631.112